Skeletal muscle index and its association with mobility among community‐dwelling older women - ZBIGNIEW M. OSSOWSKI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: The loss of muscle function and reduced mobility levels are the main reasons for the limitations of independence and disability in older people. The main aim of this study was to determine the relationship between the skeletal muscle index and mobility in older women. Material and methods: ‪The study involved 166 older women. Skeletal muscle mass and other body components were determined by bioimpedance using an InBody 720 device. Functional mobility was evaluated with the timed up-and-go test. 30-second chair stand was also used to measure the level of functional strength in lower extremities. Results: ‪The skeletal muscle index was positively correlated with functional mobility (r=-0.22; p=0.00) and 30-second chair stand (r=-0.47; p=0.00). However, the strength of lower extremities was a significantly better parameter in predicting mobility in older women than the skeletal muscle index and skeletal muscle mass. Conclusions: The functional strength of lower extremity muscles and the skeletal muscle index can have a positive effect on functional mobility in older people. The results may be helpful in clinical practice when diagnosing mobility limitations and in the process of programming physical activity of older women aimed at the prevention of sarcopenia.